PREVALENCE OF PSEUDOMONAS AERUGINOSA (P. AERUGINOSA) AND ANTIMICROBIAL SUSCEPTIBILITY PATTERNS AT A PRIVATE HOSPITAL IN SANA'A, YEMEN - Alyahawi, Ali; Monem Alhomidi, Abdul; Al-Henhena, Nawal (Universal Journal of Pharmaceutical Research, 2018)
Objective: Pseudomonas aeruginosa is clinically significant and opportunistic pathogen that causes infections in hospitalized patients. Antibiotic resistance is a major concern in clinical practice. The ongoing emergence of resistant strains that cause nosocomial infections contributes substantially to the morbidity and mortality of hospitalized patients. Objective of present study was to estimate the prevalence of Pseudomonas aeruginosa and the antimicrobial resistance patterns of P. aeruginosa isolates from hospitalized patients. Methods: The study was performed at microbiology department of a local hospital in Sana’a, Yemen. All the patients' samples of hospital departments from January, 2017 to December, 2017 were included. A Total of 2079 samples were collected during the study period. Among them, 193 strains of Pseudomonas spp. were isolated. One hundred ninety three isolates of P. aeruginosa were isolated from different clinical specimens and fully characterized by standard bacteriological procedures. Antimicrobial susceptibility pattern of each isolates was carried out by the Kirby-Bauer disk diffusion method as per CLSI guidelines. Majority of P. aeruginosa were isolated from Sputum, followed by urine specimens. Results: The isolate pathogen showed the highest sensitive to Meropenem (85.5%), followed by Amikacin (80.5%), Imipenem (80.0%), and Piperacillin/tazobactam (77.2). The highest frequency of resistance (96.2%) was observed with amoxicillin /clavulinic Acid followed by cefuroxime 94.6%, ampicillin/ sulbactam 94.5%, Co-Trimoxzole 80.5%, and norfloxacin 54%. Conclusion: The result confirmed the occurrence of drug resistance strains of P. aeruginosa. Meropenem, imipenem, and amikacin, were found to be the most effective antimicrobial drugs. It therefore calls for a very judicious, appropriate treatment regimens selection by the physicians to limit the further spread of antimicrobial resistance P. aeruginosa. Peer Review History: Received 24 May 2018; Revised 4 July; Accepted 24 September; Available online 15 September 2018 Academic Editor: Dr. Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Sania Feroz , Institute of Chemical Sciences, University of Peshawar, K.P.K Peshawar-25120, Pakistan, muskroz1@gmail.com Dr. Dalia Kamal Zaffar Ali , Modern University for technology and information, Egypt, dr.moda88@gmail.com